The American-Turkish Relationship and Its Effect on the Syrian Crisis - Al-Awamleh, Ra'ad A.; Alkhalaileh, Yusra S. (Richtmann Publishing, 2019)
The Syrian crises have been an issue of international concern since 2011. The conflict, which pitched the Bashar al-Assad led Baath regime against domestic and international oppositions, has led to a chain of events which have cascaded into social, economic, and humanitarian crisis in Turkey which shares boundary with Syria. With the toll of dead civilians and combatants exceeding a half million and displaced refugees reaching more than five million people especially women and children, the attention of the US has been drawn to the region. The need for the US and Turkey to work together is traditional. However, differing perspectives have led to different priorities. This paper examines the Turkish focus on Syria as a foreign policy dilemma and American focus on the terrorism and the humanitarian aspect of the crisis and how this have affected the crisis in Syria.